Anticancer Activity of N-Hexane Extract from Sphagneticola trilobata (L.) J.F Pruski Against MCF-7 Breast Cancer Cell - Vivi Mardina; Tisna Harmawan; Halimatussakdiah Halimatussakdiah; Syafruddin Ilyas; Masitta Tanjung (Faculty of Science and Technology Universitas Islam Negeri Ar-Raniry, 2020)
Abstract : Sphagneticola trilobata (L.) J.F. Pruski is one of the perennial herbs that is widely used by the national and international community to treat various diseases including cancer. The objective of this study was to assessment the anticancer activity of n-hexane extract of S. trilobata leaves for inhibiting the growth of MCF-7 breast cancer cells in vitro by MTT (microculture tetrazolium salt) method. The n-hexane extract of sernai leaves was obtained from the maceration process of samples that were collected from the Langsa city, Aceh. The cytotoxicity test was carried out by incubating MCF-7 cells which had been exposed to several series of sample levels, viz. 1000; 500; 100; 50; 25; 10; 5 and 1 µg/mL. LC50 values are calculated using probit analysis. The results revealed that the n-hexane extract of S. trilobata leaves was cytotoxic against breast cancer cells (MCF-7) with an LC50 value of 0.037 μg /mL.Abstrak : Sphagneticola trilobata (L.) J.F. Pruski merupakan salah satu tanaman herbal yang digunakan secara luas oleh masyarakat nasional dan internasional untuk mengobati berbagai penyakit termasuk kanker. Penelitian ini bertujuan untuk mengetahui aktivitas antikanker ekstrak n-heksana daun S. trilobata dalam menghambat pertumbuhan sel kanker payudara MCF-7 secara in vitro dengan metode MTT (microculture tetrazolium salt). Ekstrak n-heksana daun sernai diperoleh dari proses maserasi sampel yang dikoleksi dari kota Langsa, Aceh. Uji sitotoksisitas dilakukan dengan menginkubasi sel MCF-7 yang telah dipaparkan beberapa seri kadar sampel yaitu 1000, 500, 100, 50, 25, 10, 5 dan 1 µg/mL. Nilai LC50 dihitung dengan menggunakan analisa probit. Hasil penelitian menunjukkan bahwa ekstrak n-heksana daun S. trilobata bersifat sitotoksik terhadap sel kanker payudara (MCF-7) dengan harga LC50 sebesar 0,037 µg/mL.